A calixarene-based ion-selective electrode for thallium(I) detection - Chester, Ryan; Sohail, M.; Ogden, Mark; Mocerino, Mauro; Pretsch, E.; De Marco, Roland (Elsevier, 2014)
Three new calixarene Tl+ ionophores have been utilized in Tl+ ion-selective electrodes (ISEs) yieldingNernstian response in the concentration range of 10"2–10"6M TlNO3 with a non-optimized filling solution in a conventional liquid contact ISE configuration. The complex formation constants (log bIL) for two of the calixarene derivatives with thallium(I) (i.e. 6.44 and 5.85) were measured using the sandwich membrane technique, with the other ionophore immeasurable due to eventual precipitation of the ionophore during these long-term experiments. Furthermore, the unbiased selectivity coefficients for these ionophores displayed excellent selectivity against Zn2+, Ca2+, Ba2+, Cu2+, Cd2+ and Al3+ with moderate selectivity against Pb2+, Li+, Na+, H+, K+, NH4+ and Cs+, noting that silver was the only significant interferent with these calixarene-based ionophores. When optimizing the filling solution in a liquid contact ISE, it was possible to achieve a lower limit of detection of approximately 8 nM according to the IUPAC definition. Last, the new ionophores were also evaluated in four solid-contact (SC) designs leading to Nernstian response, with the best response noted with a SC electrode utilizing a gold substrate, a poly (3-octylthiophene) (POT) ion-to-electron transducer and a poly(methyl methacrylate)–poly(decylmethacrylate) (PMMA–PDMA) co-polymer membrane. This electrode exhibited a slope of 58.4 mV decade"1 and a lower detection limit of 30.2 nM. Due to the presence of an undesirable water layer and/or leaching of redox mediator from the graphite redox buffered SC, a coated wire electrode on gold and graphite redox buffered SC yielded grossly inferior detection limits against the polypyrrole/PVCSC and POT/PMMA–PDMA SC ISEs that did not display signs of a water layer or leaching of SC ingredients into the membrane.